Four-Year Efficacy and Safety of iTrack Ab-interno Canaloplasty as a Standalone Procedure and Combined with Cataract Surgery in Open-Angle Glaucoma - Koerber, Norbert; Ondrejka, Simon (Klinische Monatsblätter für Augenheilkunde, 2022)
Purpose To evaluate the long-term effectiveness of ab-interno canaloplasty (ABiC), performed with the iTrack microcatheter (Nova Eye Medical, Fremont, CA, USA), in reducing intraocular pressure (IOP) as well as the number of required glaucoma medications in patients with open-angle glaucoma (OAG).Methods In this retrospective single-center consecutive case series, 27 eyes of 21 patients (mean age 77.3 ± 5.8 years) were treated with ABiC performed as a standalone procedure or combined with cataract surgery. Patients with uncontrolled IOP OAG or controlled IOP (≤ 18 mmHg) OAG with intolerance to medications or lack of compliance were included. Patients were followed for up to 4 years following the procedure. The iTrack microcatheter was used to perform a 360-degree circumferential intubation and viscodilation of Schlemmʼs canal. Primary efficacy endpoints included IOP and the number of glaucoma medications at 12, 24, 36, and 48 months after surgery.Results In all eyes, mean IOP and number of glaucoma medications were significantly reduced from 19.8 ± 5.2 mmHg and 1.9 ± 1.00 at baseline to 14.6 ± 3 mmHg and 0.9 ± 0.8, respectively, at the 48-month follow-up (p < 0.001). IOP was stable from 12 months to 48 months (p > 0.005). After 48 months, 39% of the eyes required zero medications compared to 3.7% at baseline, and 72.2% of eyes required only one medication or less. Of all eyes, 77.8% recorded an IOP ≤ 17 mmHg. No serious complications were recorded.Conclusion iTrack ABiC performed as a standalone procedure or in combination with cataract surgery significantly reduced IOP and number of medications in patients with OAG up to 4 years after the procedure.
Keywords: intraocular pressure; ab-interno canaloplasty; MIGS; canaloplasty; minimally invasive glaucoma surgery; open-angle glaucoma